Art Education in Community - Fery Setyaningrum; Eko Haryanto; Ponimin Ponimin; Muhammad Ibnan (Universitas Negeri Semarang, 2023)
Fine arts education is an important component of the education system that provides opportunities for individuals to develop an understanding and appreciation of the arts and their creativity. This study uses a literature analysis approach to explore various sources, including scientific journals, books, and related publications. Research results This show that education art shape own significant impact _ in society . First , education art shape can increase ability think critical and creative individual . Through exploration and expression art , individual can develop ability For see the world with corner different perspectives and produce _ solution creative For problems encountered . _ Besides that is , education art appearance also plays a role in promote understanding cross culture and tolerance in society . Fine art own strength For convey a message that is profound and universal, that can build bridge between individual from background behind different culture . _ this _ can help expand perspective and reduce tension social. Next , education art shape can give significant contribution _ to development economy something society . Industry art , incl art likeness , have potency For create field work and push growth economy local . With give education art good looks , people _ can develop talent and skills required _ For success in industry art. some challenges faced _ in education art shape in society . One of them is lack of confession to importance education art shape in system formal education . Along with emphasis on lessons more academic _ traditional , art shape often ignored or considered as fields that are not important . this _ can resulted lack of source power and attention to education art shape . In framework overcome challenge this , is required effort collaborative between institution education , government , and society For increase understanding and appreciation to education art shape . importance education art shape in society.